2014
DOI: 10.1371/journal.pone.0109834
|View full text |Cite
|
Sign up to set email alerts
|

Effects of T-Type Calcium Channel Blockers on Renal Function and Aldosterone in Patients with Hypertension: A Systematic Review and Meta-Analysis

Abstract: BackgroundHigh blood pressure can cause kidney damage, which can increase blood pressure, leading to a vicious cycle. It is not clear whether the protective effects of T-type calcium channel blockers (T-type CCBs) on renal function are better than those of L-type CCBs or renin-angiotensin system (RAS) antagonists in patients with hypertension.Methods and FindingsPUBMED, MEDLINE, EMBASE, OVID, Web of Science, Cochrane, CNKI, MEDCH, VIP, and WANFANG databases were searched for clinical trials published in Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…, Abe et al . , Li & Yang ). In agreement with the mibefradil data, NNC 55‐0396 had no significant effect in the undivided patient group, but unfortunately, it was not possible to divide the patients into hypertensive ( n = 5) and normotensive ( n = 1).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…, Abe et al . , Li & Yang ). In agreement with the mibefradil data, NNC 55‐0396 had no significant effect in the undivided patient group, but unfortunately, it was not possible to divide the patients into hypertensive ( n = 5) and normotensive ( n = 1).…”
Section: Discussionmentioning
confidence: 98%
“…This distribution of calcium channels makes the T-type calcium channels in the kidney important for the regulation of renal haemodynamics (Carmines et al 1993. Clinical studies have confirmed the importance of T-type channels for renal function as treatment of patients with a combined L-and T-type blocker (benidipine) is superior to treatment with conventional calcium blockers (amlodipine) when it comes to not only blood pressure reduction but also lowering albumin/creatinine ratio and attenuation of plasma aldosterone level (Ohishi et al 2007, Ohta et al 2009, Abe et al 2011, Li & Yang 2014, Tani et al 2014. Furthermore, T-type channels might be of significance during cardiovascular disease as T-type channels are upregulated and play a larger role for contraction during augmented oxidative stress (Howitt et al 2013b).…”
mentioning
confidence: 99%
“…Recently, a meta-analysis showed that T-type CCBs are more effective than the L-type CCBs in the protection of renal function. 3 The Figure nephropathy with >50% of the participants receiving amlodipine, but patients older than 70 years were excluded. 7,8 In AASK (African American Study of Kidney Disease and Hypertension), patients with diabetes mellitus and those older than 70 years were excluded.…”
Section: Dihydropyridine Calcium Channel Blockers In the Elderly Withmentioning
confidence: 99%
“…A recent meta-analysis of 24 studies have shown that T-type blockers significantly decline proteinuria and the urinary albumin-to-creatinine ratio compared with L-type blockers, suggesting an important involvement of T-type channels for renal function (61). Altered function of the kidney vascular segments is involved in several pathological conditions, such as diabetes and hypertension (20,96).…”
Section: Kidneymentioning
confidence: 99%